Molecular line search towards the flaring 6.7-GHz methanol masers of G 24.33+0.13 and G 359.62−0.24: rare maser transitions detected. Issue 2 (22nd October 2021) - McCarthy, T P; Orosz, G; Ellingsen, S P; Breen, S L; Voronkov, M A; Burns, R A; Olech, M; Yonekura, Y; Hirota, T; Hyland, L J; Wolak, P
ABSTRACT: We have performed a molecular line search towards the flaring 6.7-GHz masers G 24.33+0.13, and G 359.6−0.24 using the Australia Telescope Compact Array. We present spectra of the 6.7-GHz class II methanol and 22.2-GHz water masers towards these sources and provide a comparison with other recent flaring events these sources have experienced. We also detect the fourth example of a 23.4-GHz class I methanol maser and the 11th example of a 4.8-GHz formaldehyde maser towards G 24.33+0.13. Alongside these results, we also observe the previously detected ammonia (3, 3) emission and report upper limits on the presence of various other cm-wavelength methanol, ammonia, and OH transitions. Our results are consistent with the flaring of G 24.33+0.13 being driven by a variable accretion rate in the host high mass young stellar object.